(untitled) (Acta Entomologica Serbica, 2020)
Here we present new findings of the hymenopteran Diphyus quadripunctorius (Müller, 1776) from three cave localities in Serbia. We examined a total of five overwintering female specimens collected during 2016, 2019 and 2020 in caves – Devojačka Pećina Cave, Sisevačka Pećina Cave in eastern Serbia and Ogorelička Pećina Cave in southeastern Serbia. Additionally, a short description of D. quadripunctorius females is provided. Its phenology, tentative host association and adaptations to cave life are also discussed.